How Different, How Similar? Comparing Key Organizational Qualities of American Public and Private Secondary Schools. Statistical Analysis Report - Baker, David; American Institutes for Research in the Behavioral Sciences, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
Although differences in the organization of public and private schools are a focus of school reform discussions, those differences are not well understood. Using data from a national sample of secondary schools in the 1990-91 Schools and Staffing Survey, conducted by the National Center for Education Statistics (NCES), this report examined organizational differences across public and private schools and among private school types. The study examines six key organizational domains: educational goals; the professionalization of principals; teacher compensation; size of administrative staff; school-based control; and curricular emphasis. Overall, the results show considerable organizational variation among different types of private schools and some significant similarities between public schools and some types of private schools. Although religious development of students is the most important goal among many private schools, comparable proportions of public, Catholic, and unaffiliated religious secondary schools hold academic excellence as their main educational goal. Although private school principals may hold fewer education credentials than their public school counterparts, there are differences across private school types. The ratio of administrative staff to faculty is larger in the private than public sector; however, there is considerable variation among private school types. Although private schools tend to have more onsite control of key administrative decisions, not all public schools lack this feature. There are few substantial sector differences in graduation requirements. Finally, after controlling for many other school characteristics, information about sector membership and private school type greatly increased prediction of a school's teacher salaries, but only modestly improved prediction of administrative staff size and the degree to which the principal is a key decision maker. In summary, school sector is not a simple organizational fault line running through the nation's schools. Eight tables and 11 figures are included. Appendices contain additional information about educational goals; details of the multiple regression analysis; tables of standard errors; a formula used in calculations; and technical notes. (Contains 45 references.) (LMI)
Sponsoring Agency: National Center for Education Statistics (ED), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Qualifications; Educational Objectives; Institutional Autonomy; Private Education; Private Schools; Public Education; Public Schools; School Based Management; School Organization; School Personnel; Secondary Education; Tables (Data); Teacher Salaries; Numerical/Quantitative Data; Reports, Research